Nowa polityka spójności Unii Europejskiej na okres 2007-2013 - Kowalik, Paweł (A New Cohesion Policy of the European Union for the Period 2007-2013, 2007)
The Structural Funds and Cohesion Fund are a key importance to the Member States in helping them strengthen their competitiveness. The enlargement of the Union to 25 Member States, and subsequently to 27 or more, will make new problems. The European Union undertook decision (in 2001) to reform a cohesion policy for the period beginning in 2007. This article presents a proposals and final solutions cohesion policy in the period 2007-2013.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 322-330